Psychometric properties of the Persian version of the training needs assessment for critical care nurses - Amir Jalali; Mostafa Bafandeh Zendeh; Azam Sharifi; Amirhossein Naghibzadeh; Leila Moradi; Jalal Karimi; Nazanin Mardani Taghvostani; Khalil Moradi (BMC Medical Education)
Abstract Background Identifying the training needs of critical care nurses is crucial for enhancing their performance and optimizing patient outcomes. This process requires a comprehensive understanding of their specific knowledge gaps and skill deficiencies. Therefore, a reliable and validated tool is necessary to assess these needs effectively. Aim This study aimed to assess the psychometric properties of the Persian version of the Training Needs of Critical Care Nurses Scale (TNCCNS) in Iran. Methods This cross-sectional methodological study evaluated the Persian version of the TNCCNS using a convenience sample of 676 intensive care unit nurses from hospitals in Kermanshah, Hamadan, and Tabriz. The study was conducted in two phases: translation and cultural adaptation, followed by an assessment of the psychometric properties of the Persian version. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed to examine the construct validity of the instrument. Additionally, internal consistency reliability was assessed using Cronbach’s alpha and McDonald’s omega coefficients, while test-retest reliability was evaluated using the Intraclass Correlation Coefficient (ICC). Data analysis was conducted using SPSS (version 27) and LISREL (version 8). Statistical significance for all analyses was set at p < 0.05. Results The results of the EFA and CFA confirmed the thirteen-factor structure with 66 items, explaining 62.337% of the total variance. CFA indicated a good model fit (RMSEA = 0.056, CFI = 0.92, NNFI / TLI = 0.94, GFI = 0.98, SRMR = 0.046, χ²/df = 2.25). Pearson correlation analysis revealed significant positive relationships between each subscale score and the overall scale score. The scale demonstrated high reliability (Cronbach’s alpha = 0.912, McDonald’s omega = 0.902) and strong stability (ICC = 0.912, 95% CI: 0.900-0.924). Conclusions The Persian TNCCNS has demonstrated robust validity and reliability, establishing itself as a valuable tool for assessing the training needs of ICU nurses in Iran. Its validation carries significant implications for both research and practice, offering a robust framework for evaluating the educational requirements of Iranian critical care nurses and the effectiveness of existing training programs. Furthermore, these findings provide essential guidance for educational administrators and policymakers in designing targeted interventions that enhance nursing competencies and improve patient care outcomes in ICU settings. Clinical trial number Not applicable.